A review on polyhouse monitoring system - Sanket Sambhaji Chivhe; Arbaz Khurshid Khan; Rutik Sunil Danavale; B. M. Borhade (International Journal of Advanced Control and System Engineering, 2025)
The integration of Internet of Things (IoT) technology in agriculture has revolutionized traditional farming practices, offering innovative solutions to enhance productivity, sustainability, and resource efficiency. This study explores the role of loT-based systems in smart agriculture, focusing on applications such as environmental monitoring, automated irrigation, crop health prediction, and precision farming. The reviewed systems utilize advanced sensors to monitor parameters like temperature, humidity, soil moisture, and light intensity, transmitting real-time data to cloud platforms for analysis. Actuators automate processes like irrigation, ventilation, and lighting, ensuring optimal conditions for crop growth while minimizing resource wastage. Several papers highlight the integration of machine learning and artificial intelligence (AI) with IoT, enabling predictive analysis for disease detection and crop yield optimization. Renewable energy sources, such as solar power, enhance the sustainability of these systems, making them viable for remote and resource-constrained areas. However, challenges such as high implementation costs, dependency on stable internet connectivity, and the need for skilled labor limit widespread adoption. This review concludes that loT-driven solutions hold immense potential to transform agriculture into a data-driven domain, addressing global challenges like food security and climate change. Future research should focus on improving scalability, affordability, and integrating emerging technologies like blockchain and edge computing for enhanced efficiency and security.
Keywords: Internet of things (IoT); Precision Farming; Smart Agriculture; automated irrigation; environmental -monitoring